A qualitative study of leucoanthocyanins in kaong (Arenga pinnat) - Majaba, Norma M.; Acevedo, Teresita P. (1971.)
ABSTRACT The nature of the leucoanthocyanins in kaong (Arenga pinnata) was studied. Three kaong samples were used: fresh and untreated; fresh and treated; and canned and treated. The leucoanthocyanin was extracted in the form of anthocyanidin by the use of n-butanol-HCl reagent. Color reaction with this reagent at various times and temperatures of heating was determined. Paper chromatographic analysis, color reaction with ferric chloride-ferricyanide reagent and absorbance studies were also performed. Results of the chemical tests showed that the anthocyanidin obtained from kaong was similar to pelargonidin obtained from strawberries.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Kaong